Reformation, Revival, and Rebirth in Anglican Evangelical Thought, c.1780–c.1830 - Atkins, Gareth ca. 20./21. Jh. (Studies in church history, 2008)
For Anglican Evangelicals, terms like ‘awakening’ and ‘revival’ pointed rather to reinvigoration and the recovery of old glories than to some new and disturbing disjunction. Those seeking change, remarked Rowland Hill, would do well to follow the example of the reformers, who ‘did not innovate, but renovate, they did not institute, they only reformed.’ Nevertheless, this still left many - like Hill -balancing their urge to reform on the one hand with the importance of Anglican ‘regularity’ on the other. Several initiatives bore the mark of this tension. For example, the foundation of the Church Missionary Society (CMS) in 1799 owed much to frustration with the inactivity of the Society for Promoting Christian Knowledge (SPCK) and the Society for the Propagation of the Gospel (SPG). The new society was ‘founded upon the Church-principle, not the High Church principle’, remarked John Venn, who stressed that it was possible to express Gospel zeal within a solidly Anglican framework. As the Missionary Magazine commented perceptively, ‘a set of people will no doubt contribute to this whose predilection for the Church and dislike to Methodists and Dissenters, would have effectively kept them from aiding the [London Missionary Society]’. The Christian Observer, founded in 1802 to be the periodical mouthpiece of ‘moderate’ Evangelicalism, evinced the same concerns in its first number, when it promised ‘to correct the false sentiments of the religious world, and to explain the principles of the Church’. As the leading Evangelical ‘regulars’ maintained, only this uneasy balancing act could bring far-reaching change.